2022
DOI: 10.58286/27286
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis and Digital Image Correlation Techniques for a Suspension Bridge

Abstract: Bridge inspection is critical to safe transportation, especially in highly urbanized areas. Frequent inspection invoked by the un-scheduled maintenance for bridges is often subjected to the availability of NDT service providers. Hence the objective of the current research is to provide an economical NDT technique for the maintenance crew. Digital image correlation techniques can be cost-effective for the displacement measurement of highway bridges using merely one high-resolution camera. The vibration analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The investigation demonstrated the good agreement between data obtained from two setups [46], thus confirming the applicability of the approach for urban areas without preparing of investigated surface. Similarly, vibration analysis of the suspension bridge, subjected to pedestrian loadings, performed by Yung-Chiang Lin et al, 2022 [47] has shown satisfactory results for quick remote assessment of the bridge. Similarly, heavy trucks' vehicle loading tests have confirmed the effectiveness of the method, as was reported in several studies [1, [48][49][50][51][52].…”
Section: Application Of the Dic Methods Formentioning
confidence: 99%
“…The investigation demonstrated the good agreement between data obtained from two setups [46], thus confirming the applicability of the approach for urban areas without preparing of investigated surface. Similarly, vibration analysis of the suspension bridge, subjected to pedestrian loadings, performed by Yung-Chiang Lin et al, 2022 [47] has shown satisfactory results for quick remote assessment of the bridge. Similarly, heavy trucks' vehicle loading tests have confirmed the effectiveness of the method, as was reported in several studies [1, [48][49][50][51][52].…”
Section: Application Of the Dic Methods Formentioning
confidence: 99%